Effectiveness of Helping Babies Breathe Training on Knowledge and Skills for Health Professional and Medical Doctors at Nepalgunj Medical College - Kanodia, Piush; Mahaseth, Sameer; Parajuli, Bishnu (Journal of Nepalgunj Medical College, 2022)
Introduction: Neonatal death is an emerging challenge and a basic neonatal resuscitation within the first few minutes of life can substantially prevent neonatal mortality. Aims: To reduce neonatal mortality from birth asphyxia and development of the low cost neonatal neonatal resuscitation tool. Methods: The educational effectiveness of helping baby breathe training on newborn simulator, knowledge of trainees from Doctors, Nurses and Medical Students was evaluated before and after training on 19th & 20th November 2021, 10th & 11th December 2021 and 6th & 7th January 2022 respectively. A post course practical skills evaluation was performed on a Neonatalie Newborn Simulator. Participants underwent a two days training course of five hours each day. Results: Seventy eight participants had completed the course. The percentage of correct answers on a written test significantly increased from 82% to 99% after training. 100% of the trainees achieved passing scores. Conclusion: The trainees who participate in helping baby breathe training can significantly improve their knowledge and skills on simulators.